Ujaran Ilokusi dalam Film "Jatuh Cinta Seperti di Film-Film" Karya Yandy Laurens - Kudadiri, Chrisnatalia; Mulyadi, Mulyadi (Deskripsi Bahasa, 2025)
This study aimed at analyzing and describe the illocutionary speech acts found in a movie “Jatuh Cinta Seperti di Film-Film” using a pragmatic approach. The study was based on Searle's theory, which categorizes illocutionary speech acts into five types: assertive, directive, expressive, commissive, and declarative. The object of this research was the movie “Jatuh Cinta Seperti di Film-Film”, directed by Yandy Laurens. The research data consisted of dialogues or utterances in the movie that contain illocutionary speech acts. Based on its form, this research was qualitative, while in terms of purpose, it is descriptive. The method used was observation and note-taking, with the researcher acting as the primary research instrument. Based on data analysis, it was concluded that four types of illocutionary speech acts appear in the film: assertive, directive, expressive, and commissive. Assertive speech acts were the most frequently used, appearing in 148 utterances (58.5%), followed by directive speech acts with 72 utterances (28.46%), expressive speech acts with 29 utterances (11.46%), and commissive speech acts with 4 utterances (1.58%). These findings indicated that assertive speech acts are the most dominant in the film “Jatuh Cinta Seperti di Film-Film”. This dominance was due to the storyline, which focuses on the reunion of the two main characters, resulting in dialogues that often function to convey information, opinions, or statements. Meanwhile, the absence of declarative speech acts suggested that the movie does not focus on formal or institutional situations.